Adam and Eve in the Qur’an: A Mimetic Perspective - Achtar, Ahmad (Mimetic theory and Islam, 2019)
This chapter considers the Quranic traditions of Adam and Eve from a mimetic perspective. Three texts are examined, from Suras 2, 20 and 7. Consideration is given to the exact nature of the object of prohibition. Two alternatives are considered: the consequence is that they will be like ‘angels’ or like ‘kings.’ The second reading appears to be more plausible. Since there are no ‘kings’ on whom the first couple can model themselves, their desire can only derive from God himself and what they have witnessed of God’s sovereign power. It is not their desire for transcendence which is condemned but their disobedience, that is, the idolatrous self-affirmation which causes them to fulfil this desire apart from and without God’s guidance.